RESPONS SAWI PAGODA (Brassica narinosa) TERHADAP KETEBALAN MULSA JERAMI PADI DAN BERBAGAI KONSENTRASI PUPUK ORGANIK CAIR - Wawan Agung Setiawan; Syafiuddin Syafiuddin; Jamaludin Jamaludin; Yatmin Yatmin (STIPER Dharma Wacana Metro, 2019)
Tatsoi is included in the Brassicaceae family which contains protein, fat, fiber, calcium and several vitamins making the tatsoi an exclusive vegetable. Tatsoi is not widely cultivated by farmers, so there are not many guidelines for the cultivation. To increase the growth and yield of tatsoi can be done using mulch and Liquid Organic Fertilizer. This study aims to determine effect of the thickness of rice straw mulch and variations concentration of liquid organic fertilizer on the growth and yield of tatsoi. The research was conducted at the STIPER Dharma Wacana experimental garden from November to December 2018. This study used a randomized block design in two factors. The first factor is the thickness of straw mulch which consists of 3 levels (without mulch, rice straw mulch 10 tonnes/ha, and rice straw mulch 20 tonnes/ha). The second factor is the concentration of liquid organic fertilizer which consists of 3 levels (control, 2 ml / l, and 4 ml / l). The results showed that the thickness of the rice straw mulch had no significant effect on the growth and yield of Tatsoi. The addition of 2 ml / l and 4 ml / l liquid organic fertilizer significantly increased the growth and yield of tatsoi compared without liquid organic fertilizer as indicated by the variables of plant height, number of leaves, crown diameter, yield per plot, wet weight salable yield, and yield per hectare. There is no interaction between the two factors.